2004
DOI: 10.1161/01.str.0000115754.20124.4f
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 Polymorphisms Are Not Associated With Spontaneous Cervical Artery Dissection

Abstract: Background and Purpose-Cervical artery dissection (CAD) is a common cause of ischemic stroke in young adults.Alteration in the structure of the vascular extracellular matrix has been described in CAD. Matrix metalloproteinases (MMPs) degrade extracellular matrix proteins and can lead to vascular damage. Methods-We tested 2 different MMP-9 DNA polymorphisms, a CA repeat and a cytosine to thymidine transition in the promotor sequence, for frequency in 52 patients with CAD. We compared the results with those of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…2,58,63 Additional genetic factors have also been implicated in spontaneous carotid dissection. 30,[64][65][66][67][68][69] In addition, studies have demonstrated associations with carotid artery dissection in variants of 3 different candidate genes. 30,[64][65][66][67][68][69] In addition, studies have demonstrated associations with carotid artery dissection in variants of 3 different candidate genes.…”
Section: Intrinsic Factorsmentioning
confidence: 99%
“…2,58,63 Additional genetic factors have also been implicated in spontaneous carotid dissection. 30,[64][65][66][67][68][69] In addition, studies have demonstrated associations with carotid artery dissection in variants of 3 different candidate genes. 30,[64][65][66][67][68][69] In addition, studies have demonstrated associations with carotid artery dissection in variants of 3 different candidate genes.…”
Section: Intrinsic Factorsmentioning
confidence: 99%
“…Despite a biological plausible a priori hypothesis, our results do not support a role for MTHFR/C677T in the aetiology of carotid dissection. Two other candidates, MMP-9 [28] and α 1 -antitrypsin deficiency [29], have been studied in carotid dissection but have not been replicated. Lack of studies therefore prevented these for inclusion into our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…No differences were found in the allelic distribution of either polymorphism, thereby indicating that alleles of these well-characterized functional polymorphisms of MMP-9 gene were not associated with structural alterations in the matrix of vessels of patients with cervical artery dissection. 101 Zhai and coworkers genotyped 7 polymorphisms [MMP-1 -1607 1G/2G (rs1799750), MMP-2 C-1306T (rs243865) and C-735T (rs2285053), MMP-3 -1612 5A/6A (rs3025058), MMP-9 C-1562T (rs3918242), MMP-12 G-82A (rs2276109), and MMP-13 G-77A (rs17860523)] in 434 incident patients with hepatocellular carcinoma and 480 controls to explore MMP polymorphisms having any bearing on the risk of HCC. 102 Results of another study suggested that the polymorphisms MMP-7 A-181G, MMP-8 C-799T, and MMP-21 C572T may not play a major role in mediating susceptibility to hepatocellular carcinoma.…”
Section: Mps and Polymorphismsmentioning
confidence: 99%